Low Power/ High Speed Design in VLSI with the application of Pipelining and Parallel processing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The main objectives of any VLSI design are Power, Delay andArea. Minimizing all the objectives is a challenge in presentsituation but all efforts to achieve one of these can lead to abetter design. This paper proposes an EDA tool for low power/high speed VLSI design, which solves any DFG to estimate thespeed of operation and the percentage reduction in the powerconsumption using pipelining and parallel processing concepts